NIPBL rearrangements in Cornelia de Lange syndrome: evidence for replicative mechanism and genotype–phenotype correlation - Pehlivan, Davut; Hullings, Melanie; Carvalho, Claudia M.B.; Gonzaga-Jauregui, Claudia G.; Loy, Elizabeth; Jackson, Laird G.; Krantz, Ian D.; Deardorff, Matthew A.; Lupski, James R. (Genetics in medicine, 2012)
Purpose: Cornelia de Lange syndrome (CdLS) is a multisystem congenital anomaly disorder characterized by mental retardation, limb abnormalities, distinctive facial features, and hirsutism. Mutations in three genes involved in sister chromatid cohesion, NIPBL , SMC1A , and SMC3 , account for ~55% of CdLS cases. The molecular etiology of a significant fraction of CdLS cases remains unknown. We hypothesized that large genomic rearrangements of cohesin complex subunit genes may play a role in the molecular etiology of this disorder. Methods: Custom high-resolution oligonucleotide array comparative genomic hybridization analyses interrogating candidate cohesin genes and breakpoint junction sequencing of identified genomic variants were performed. Results: Of the 162 patients with CdLS, for whom mutations in known CdLS genes were previously negative by sequencing, deletions containing NIPBL exons were observed in 7 subjects (~5%). Breakpoint sequences in five patients implicated microhomology-mediated replicative mechanisms—such as serial replication slippage and fork stalling and template switching/microhomology-mediated break-induced replication—as a potential predominant contributor to these copy number variations. Most deletions are predicted to result in haploinsufficiency due to heterozygous loss-of-function mutations; such mutations may result in a more severe CdLS phenotype. Conclusion: Our findings suggest a potential clinical utility to testing for copy number variations involving NIPBL when clinically diagnosed CdLS cases are mutation-negative by DNA-sequencing studies. Genet Med 2012:14(3):313–322